Analisis Kinerja Dinas Pemberdayaan Perempuan dan Perlindungan Anak dalam Menangani Kekerasan Fisik terhadap Anak di Kabupaten Simalungun - Apni Nurita Saragih; Ramsul Nababan (Journal on Education, 2024)
Physical violence is an action that injures a person's body or property, such as hitting, pinching, pulling, kicking, pushing, robbing, or damaging property. Nowadays there are many cases where physical violence is often experienced by children. One of the institutions that handles physical violence against children is the Women's Empowerment and Child Protection Service. This research aims to determine the performance of the Women's Empowerment and Child Protection Service in Simalungun Regency in handling cases of physical violence against children and to examine the inhibiting factors that occur in the service's performance. This type of research uses qualitative methods with the approach used is a descriptive approach, namely observation and direct contact with relevant informants to obtain information. The results of this research found that the performance of the Simalungun Regency Women's Empowerment and Child Protection service was quite good, where almost all of the 5 performance measurement indicators carried out by researchers were met, although not optimal. However, apart from that, the factors inhibiting the performance of the Department are the limited human resources and number of officers providing services for physical violence against children, the limited budget for services for physical violence against children, the public's understanding of the Child Protection Law is still low and there is still a culture of shame and low public awareness of reporting to the authorities if physical violence occurs against children.